PENDAMPINGAN SISWA SMP DAN SMA DALAM MEMAINKAN ALAT MUSIK TRADISIONAL SASANDO DAUN UNTUK MELESTARIKAN ALAT MUSIK TRADISIONAL ETNIK NUSA TENGGARA TIMUR - Muntasir, Muntasir; Jutomo, Lewi; Edon, Caro David Hadel; Mayners, Marline; Awaluddin, Sri Prilmayanti (Dewan Pimpinan Daerah (DPD) Forum Dosen Indonesia JATIM, 2020)
This community service aims to empower junior and senior high school students to improve their knowledge, abilities and skills in playing NTT ethnic traditional musical instruments as an effort to preserve local culture, especially traditional musical instruments. Implementation methods are designed based on community empowerment methods including identification of schools and target participants, preparation of training tools and materials, provision of materials, introduction of sasando daun traditional musical instruments, recognition of tone and sound, training and use of playing sasando daun traditional musical instruments and monitoring and evaluation and sustainability. This activity is carried out on St. Catholic Catholic Middle School students Familia and Kupang Superior Generation Christian High School, each 20 students. The results of the activity showed that as many as 40 participants were able to play the Sasando Daun  traditional musical instrument skillfully, skillfully and well. It is expected that with the presence of 40 students the students will be able to direct and motivate other students to play the traditional Sasando Daun musical instrument so as to be able to preserve the NTT ethnic culture, especially maintaining the ability to play this instrument. For the continuation of the activities of all these students will be included in the appearance of the traditional Sasando Daun musical instrument play in various events in Kupang and outside Kupang and formed the Sasando Traditional Music Art Unit.